Paciente embarazada de 20 años de edad con bajo peso. - Rodríguez Chichande, Joel Oton (2021)
The present clinical case is about a 20-year-old patient with a low weight pregnancy, lives in the CDG parish of the city of Babahoyo, which through an anamnesis and nutritional assessment was diagnosed a low weight pregnancy with deficiency of adequate nutritional intake. The medications you take during pregnancy are: iron + folic acid and vitamin c. The diet carried out by the pregnant patient is very deficient for her stage of pregnancy, due to its low economic availability and its shortcomings in recognizing foods that are rich in iron, folic acid, vitamin C, vitamin D, calcium, magnesium, etc. Which leads to a low weight pregnancy with future complications or risks during pregnancy which affects both the child and the mother. These causes of macro and micronutrient deficiencies before, during and after pregnancy lead to the mother and child having low weight in pregnancy and low birth weight in the child, for which the immune system is very deficient to combat any type of microorganism, virus or bacteria. Due to this nutrient deficit, the child is exposed to pathologies: anemia, hypoglycemia, hypothermia, hypocalcemia, etc. Those can be reflected from the acute to the chronic and is not advisable for both. An individualized nutritional plan is carried out for the patient, taking into account her socioeconomic situation and her low weight condition, the type of diet that will be prescribed will be a diet high in carbohydrates, hyperprotein, high in unsaturated fats, hypo sodium fractionated in 5 meals a day, is characterized by being a diet, rich in carbohydrates, proteins, unsaturated fats with omega 3 and 6, rich in folic acid, iron, calcium, low in sodium and high in fiber that will help stabilize glycemia levels and blood pressure, constipation of the patient. A follow-up and monitoring plan is carried out on the patient with a 33-week gestation pregnancy with low weight in the course of a month, favorable results were observed in the increase of adequate Weight Gain that leads to a favorable health condition of the patient and fetus.